2014
DOI: 10.1536/ihj.13-224
|View full text |Cite
|
Sign up to set email alerts
|

Six-Minute Walk Distance Is an Independent Predictor of Hospital Readmission in Patients With Chronic Heart Failure

Abstract: SummaryPatients with chronic heart failure (CHF) are frequently readmitted to the hospital due to disease progression. Although a shorter 6-minute walk distance (6MWD) is correlated with poor prognosis, 6MWD is not considered a clinical indicator for predicting hospital readmission.We investigated whether 6MWD measured at the time of hospital discharge predicted readmission due to heart failure in CHF patients.Patients admitted to the hospital for the first time due to heart failure were enrolled. After 6MWD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 26 publications
(24 reference statements)
1
49
1
2
Order By: Relevance
“…Furthermore, in order to improve the assessment of functional capacity, future work could incorporate more objective measures such as a sixminute walk test. Previous studies have demonstrated that a sixminute walk distance is an independent predictor of hospital admission in patients with chronic heart failure [45][46][47]. Separating subjects according to the results of a six-minute walk test, rather than the arguably subjective NYHA classification, may have improved the strength of our study and enabled correlations between these results and biomarker concentrations.…”
Section: Limitations Of the Studymentioning
confidence: 87%
“…Furthermore, in order to improve the assessment of functional capacity, future work could incorporate more objective measures such as a sixminute walk test. Previous studies have demonstrated that a sixminute walk distance is an independent predictor of hospital admission in patients with chronic heart failure [45][46][47]. Separating subjects according to the results of a six-minute walk test, rather than the arguably subjective NYHA classification, may have improved the strength of our study and enabled correlations between these results and biomarker concentrations.…”
Section: Limitations Of the Studymentioning
confidence: 87%
“…63-65 , la prueba de marcha de 6 min es la más popular, siendo en la actualidad el protocolo simple de ejercicio de referencia en la EPOC y otras enfermedades [66][67][68][69][70][71][72] . Tiene un buen nivel de estandarización 63,73,74 , con una reproducibilidad razonable 75 , y es muy útil para la evaluación del estado funcional de los pacientes, así como para medir los efectos de diferentes intervenciones en una gran variedad de enfermedades crónicas [76][77][78][79][80][81] .…”
Section: Evaluación De La Capacidad De Esfuerzo: Prueba De Marcha De unclassified
“…Evidence of cardiac rehabilitation has been shown in patients with heart disease. [10][11][12][13] However, there is little evidence of nutritional management in HF patients and the most appropriate nutritional assessment has not yet been established.…”
mentioning
confidence: 99%